Endoscopic or Microscopic Tympanoplasty Advantages and Disadvantages: A Theory Domain Systematic Review - Bianchini, Ana Júlia; Berlitz, Vitória Gabriela; Mocelin, Aurenzo Gonçalves; Ribeiro, Juliana Ferraz; Keruk, João Gabriel; Hamerschmidt, Rogério (International Archives of Otorhinolaryngology, 2022)
Introduction Tympanoplasty is a reparative surgery that has multiple indications. The aid of a microscope or an endoscope is necessary to carry out the procedure. The classic method utilizes the microscope; however, in the recent decades, the endoscope has been popular. Although many articles try to compare these two techniques, there is still no robust evidence that confirms the superiority of either technique. In the present work, we seek to perform a systematic review contribute with this.Objectives The present systematic review attempted to compare endoscopic and microscopic surgery techniques and to discover whether there would be superiority in the results of any of them, based on data currently available in the literature.Data Synthesis The objectives of the present review were organized according to the PICO planning and strategy adapted for systematic reviews. The inclusion and exclusion criteria were established aiming to select only select primary data. The main medical databases were searched using an optimized search string with appropriate descriptors. The searched databases were MEDLINE, LILACS, SciELO, and EMBASE. A total of 99 studies were selected and 38 were fully assessed after the inclusion criteria were applied. All included articles were reviewed by all authors and their results were discussed and summarized.Conclusion The endoscopic technique was shown to be a safer technique comparable in effectiveness to the use of microscopy. In addition, it provides possible advantages such as shortening the surgical time and better postoperative pain outcomes.
Keywords: tympanoplasty; endoscopes; microsurgery; otologic surgical procedure; natural orifice endoscopic surgery